Enhancing students’ participation through question and answer on SMAN 2 Sungai Kakap Kubu Raya - Sada, Clarry; Wiranto, Irfan Agung (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The aim of this research is to enhance students’ participation by using question and answer technique. Therefore, the question of the research is how does Question and Answer enhance students’ participation on the 11th grade students of SMAN 2 Sungai KakapKubu Raya in academic year 2021/2022?”. The research was conducted in classroom action research design. The research was conducted in two cycles. On the first cycle, there were only some students who actively participated in the learning activity. On the second cycle, most of the students were very active. The problem about lack of participation was solved. Therefore, it is concluded that question and answer technique is useful in improving students’ participation.